Observation of electroweak production of Wγ with two jets in proton-proton collisions at √s = 13 TeV; Physics Letters B; Vol. 811 - Sirunyan А. М.; Tumasyan A. R.; Adam W. Wolfgang; Ambrogi F. Federico; Tyurin N. E. Nikolay Evgenjevich; Babaev A. A. Anton Anatoljevich; Sukhikh L. G. Leonid Grigorievich (2020, 2020)
Title screen